REVISITING CURRICULUM THEORY: POST-FOUNDATIONAL SHIFTS IN 21ST-CENTURY KNOWLEDGE CONSTRUCTION: A SYSTEMATIC LITERATURE REVIEW - Deni Haryadi; Wahyu Widada; Sungkem Tri Wahyuni; Badeni Badeni; Eko Risdianto (International Journal of Educational Review, 2026)
This systematic literature review examines post-foundational shifts in curriculum theory through 13 studies appraised using PRISMA and MMAT 2018. The findings identify four themes: the crisis of foundational curriculum theory; the rise of plural epistemologies; the mediation of knowledge construction through language, power, culture, and digitality; and a synthesised model of curriculum transformation. The study’s novelty lies in integrating decolonial, relational, linguistic, and adaptive debates into one post-foundational framework and proposing a four-movement model that offers a concise conceptual vocabulary for interpreting contemporary curriculum transformation across diverse educational contexts.